2007
DOI: 10.1158/0008-5472.can-06-4475
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Profiles Reveal Ubiquilin 1 as a Humoral Immune Response Target in Lung Adenocarcinoma

Abstract: There is considerable evidence that the presence of cancer can elicit a humoral immune response to specific proteins in the host, and these resulting autoantibodies may have potential as noninvasive biomarkers. To characterize the autoantibody repertoire present in the sera of patients with lung adenocarcinoma, we developed a high-density peptide microarray derived from biopanning a lung cancer phage display library. Using a 2,304-element microarray, we interrogated a total of 250 sera from Michigan lung cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 49 publications
5
67
0
1
Order By: Relevance
“…Fingerprinting of enriched serum antibodies with phage display offers a more direct combinatorial screening for antibody epitopes and has identified numerous biologically relevant antigens (7)(8)(9)(10)(11)(12). Moreover, studies from other laboratories have indicated clinical relevance in cancer diagnostics for antibodies against molecules such as osteopontin (20,21), isoprostanes (22), and CXCL13 (23), among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingerprinting of enriched serum antibodies with phage display offers a more direct combinatorial screening for antibody epitopes and has identified numerous biologically relevant antigens (7)(8)(9)(10)(11)(12). Moreover, studies from other laboratories have indicated clinical relevance in cancer diagnostics for antibodies against molecules such as osteopontin (20,21), isoprostanes (22), and CXCL13 (23), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Specific autoantibodies and their cognate tumor-associated antigens have been characterized, e.g., GRP78 for prostate cancer (9), HSP90 for ovarian cancer (8), ubiquilin 1 in lung cancer (10), and annexin XI-A in breast cancer (11). In addition, phage-based screening approaches have been developed for high-throughput profiling of immunogenic antigens for prostate cancer (12).…”
mentioning
confidence: 99%
“…We wanted to determine if variation in Ubqln mRNA could be observed in human cancer samples. Previous work had shown that Ubqln mRNA and protein levels are increased in primary lung adenocarcinomas, a cancer type that also features high BCLb protein levels (14,37). To build on these observations, we examined Ubqln mRNA in an independent set of 46 primary adenocarcinomas and matched normal lung samples (38).…”
mentioning
confidence: 99%
“…Arrays can be used with high throughput to determine patterns of antigens recognized by autoantibodies during the course of diseases, such as autoimmunity or cancer (1)(2)(3)(4)(5)(6)(7)(8)(9), as well as a way to characterize the repertoire of serological responses in healthy individuals (10). Defined protein collections assembled from phage expression systems or purified from recombinant sources were used to detect antibody responses in the serum of ovarian (11,12), breast (13), colorectal (2), pancreatic (14), or lung (15,16) cancer patients, and some of these responses appear to have diagnostic significance. In addition, protein array tools are also useful to measure changes in antibody responses to vaccination or immunotherapies, although it has yet to be applied to the monitoring of cancer treatments (17,18).…”
mentioning
confidence: 99%